Alguns resultados da teoria de operadores multilineares absolutamente somantes - Silvestre, Renato Bezerra (2016)
The purpose of the present work is to present some results related to multilinear theory of absolutely summing operators. More precisely, we study generalizations of inequalities of Khinchin and Kahane and a characterization of Banach spaces of type 2, due to D. Popa, through absolutely and almost summing multilinear operators.